Hemangiopericytoma as the cause of Collet-Sicard syndrome - (:unkn) unknown (My University, 1990)
Collet-Sicard syndrome is one of the jugular foramen syndromes in which the last four cranial nerves are involved whereas the sympathetic plexus is spared. It is very uncommon to find facial paralysis associated to this syndrome and most interestingly, a hemangiopericytoma at this location to cause all these paralyses. We have not been able to find a similar case in the literature, and thus present our case.
Keywords: Collet-Sicard syndrome; Hemangiopericytoma